KAJIAN TEORITIS: ANALISIS JARINGAN KOMUNIKASI INTERPERSONAL - Asri Sulistiawati (Universitas Teuku Umar, 2017)
Communication network analysis is one of method that can be used to identify the interaction of individuals in the group. This method not only focused on the individual and the social unit itself, but also the quality of the relationship between social units. This study aims to identify part of communication network concept such as interpersonal communication network. This article contains of a number of concepts related to interpersonal communication networks. Furthemore, this article try to give some descriptions about some researchs that concern about interpersonal comunication network. Therefore, this study aims to identify indicators that researchers often use in their research.Keyword: Communication network, interpersonal communication